2018
DOI: 10.1016/j.apsusc.2018.03.103
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical bonding in cold spraying of dissimilar materials

Abstract: Impact morphology and deformation of single splats were modelled through FEM simulations using PTW plasticity model to account for large strain rates.Annealing experiments and consequently formed interfacial intermetallics layer were investigated.Correlation of interfacial intermetallics pattern with highly strained interface area, predicted by modelling, present a new insight to the extent of particle/substrate metallurgical bonding. Metallurgical bonding of a particle/substrate is more likely to be found at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…This implies that Ni is the dominant diffuser, in accordance with the literature on interdiffusion of Ni - Ti system (Ref 47 ). A close look at Ni/Ti splat interfaces shows that thin intermetallics did not form continuously at the whole interface area and that they all present various thicknesses, suggesting a role of localized deformation and bonding in the kinetics of intermetallic phase nucleation at Ni/Ti interface (Ref 33 ). Similarly to what was observed for the annealing temperature of 400°C, Ni splats exhibit very fine grains at the splat boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that Ni is the dominant diffuser, in accordance with the literature on interdiffusion of Ni - Ti system (Ref 47 ). A close look at Ni/Ti splat interfaces shows that thin intermetallics did not form continuously at the whole interface area and that they all present various thicknesses, suggesting a role of localized deformation and bonding in the kinetics of intermetallic phase nucleation at Ni/Ti interface (Ref 33 ). Similarly to what was observed for the annealing temperature of 400°C, Ni splats exhibit very fine grains at the splat boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…There are quite a few mechanisms of bonding proposed in the literature [29,50] some of which are under debate. Some of these debates include whether or not adiabatic shear instability is required for bonding [51,52], the roles of jetting-outward ejection of material from the particle-substrate interface, native surface oxide layer [29,53], interfacial melting [54][55][56], and interface solid-state amorphization [57,58]; these mechanisms will be examined in details in the latter section.…”
Section: Mechanisms Of Bonding and Objective Of The Studymentioning
confidence: 99%
“…In contrast, for metallic material the general form of interface bonding can be characterized by the contact area, time, temperature and recoverable resilience, conducted with distinct conditions of adiabatic shear instability. Nikbakht et al (2018) studied the asymmetrical bonding in cold gas dynamic spraying of two dissimilar materials (Ni and Ti). Experimental results showed that with the increase in impact velocity, the bonding enhance from the circumference to the center of the interfaces.…”
Section: Bonding Mechanism In Cold Spraymentioning
confidence: 99%